Effect of Lateral Column Lengthening on Subtalar Motion in a Cadaveric Model. (April 2021) - Harris, Mitchell C.; Hedrick, Brittany N.; Zide, Jacob R.; Thomas, Danielle M.; Shivers, Claire; Siebert, Matthew J.; Pierce, William A.; Kanaan, Yassine; Riccio, Anthony I.
Background: Although lengthening of the lateral column through a calcaneal neck osteotomy is an integral component of flatfoot reconstruction in younger patients with flexible planovalgus deformities, concern exists as to the effect of this intra-articular osteotomy on subtalar motion. The purpose of this study was to quantify the alterations in subtalar motion following lateral column lengthening (LCL). Methods: The subtalar motion of 14 fresh-frozen cadaveric feet was assessed using a 3-dimensional motion capture system and materials testing system (MTS). Following potting of the tibia and calcaneus, optic markers were placed into the tibia, calcaneus, and talus. The MTS was used to apply a rotational force across the subtalar joint to a torque of 5 Nm. Abduction/adduction, supination/pronation, and plantarflexion/dorsiflexion about the talus were recorded. Specimens then underwent LCL via a calcaneal neck osteotomy, which was maintained with a 12-mm porous titanium wedge. Repeat subtalar motion analysis was performed and compared to pre-LCL motion using a paired t test. Results: No statistically significant differences in subtalar abduction/adduction (10.9 vs 11.8 degrees, P = .48), supination/pronation (3.5 vs 2.7 degrees, P = .31), or plantarflexion/dorsiflexion (1.6 vs 1.0 degrees, P = .10) were identified following LCL. Conclusion: No significant changes in subtalar motion were observed following lateral column lengthening in this biomechanical cadaveric study. Clinical Relevance: Although these findings do not obviate concerns of clinical subtalar stiffness following lateral column lengthening for planovalgus deformity correction, they suggest that diminished postoperative subtalar motion, when it occurs, may be due to soft tissue scarring rather than alterations of joint anatomy.